Exploring the Relationship between Learning Styles and Strategies for Secondary School Students in Thailand - Stanescu, Irina Mihaela (Beyond Words, 2017)
The study explores the meaning of learning styles and strategies and attempts to find a relationship between the two in the context of English language learning. The research is conducted in Thailand with 22 grade six students and it examines some of the definitions and characteristics of learning strategies and learning styles as described by scholars in the field of SLA. The results gathered using qualitative and quantitative data, show that that the majority of the students are visual style learners and multi-modal learners. Based on the data collected, there is no concrete relationship between learning style and the use of learning strategies. Even so, the topic leaves many areas open for exploration, in particular, the learner’s metacognitive awareness of learning style and conscious learning strategy use and how this may improve his second language acquisition. The research also sheds a light on the learning strategies used by secondary school students in their L2 classroom as described by data collected through interviews.